2016
DOI: 10.1002/aic.15214
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol perm‐selective B‐ZSM‐5 zeolite membranes from dilute solutions

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Boron-substituted MFI (B-ZSM-5) zeolite membranes with high pervaporation (PV) performance were prepared onto seeded inexpensive macroporous a-Al 2 O 3 supports from dilute solution and explored for the separation of ethanol/water mixtures by PV. The effects of several parameters on microstructures and PV performance of the B-ZSM-5 membranes were examined systematically, including the seed size, synthesis temperature, crystallization time, B/Si ratio, H 2 O/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The PV performances of the membranes fabricated in the present study were also compared with those of silicalite-1 membranes prepared on tubular supports by HT [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] and on silica supports by the gel-free SAC method [22] in previous studies (Figure 5). The silicalite-1 membranes fabricated in this study on the silica-particle-coated supports using the gel-free SAC method showed very high PV performances as well as highest membrane selectivity (α mem ) compared with the previously reported membranes [28].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The PV performances of the membranes fabricated in the present study were also compared with those of silicalite-1 membranes prepared on tubular supports by HT [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] and on silica supports by the gel-free SAC method [22] in previous studies (Figure 5). The silicalite-1 membranes fabricated in this study on the silica-particle-coated supports using the gel-free SAC method showed very high PV performances as well as highest membrane selectivity (α mem ) compared with the previously reported membranes [28].…”
Section: Resultsmentioning
confidence: 90%
“…Silicalite-1 membranes are generally prepared by hydrothermal synthesis (HT) using an in-situ crystallization or secondary growth method [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. In both cases, the synthetic gel is prepared by mixing a silica source, a structure-directing agent (SDA), a mineralizing agent, and water and immersing the support in this mixture to synthesize the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…From the single pervaporation tests of alkylbenzenes, the flux of p-and m-xylene were 0.58 and 0.26 kg m -2 h -1 , respectively, and that of 0.07 kg m -2 h -1 for 1,3,5-trimethylbenzene was much lower than those for xylenes. This could be explained by the molecular sieving effect (the molecular sizes of p-, mxylene, and 1,3,5-trimethylbenzene are 0.67, 0.71, and 0.76 nm, [5] EtOH/water ZIF-71 5 298 2.60 6.88 [27] EtOH/water silicalite-1 10 333 1.4 85 [28] EtOH/water B-ZSM-5 10 333 2.6 55 [29] EtOH/water ZIF-8/PDMS [a] 5 333 1.23 9.9 [30] EtOH/water MIL-53/PDMS [a] 5 353 5.47 11.1 [31] EtOH/water silicalite-1/PDMS [a] 5 323 5.52 15.5 [32] MeOH respectively). Thus, on the basis of its pore size, these results indicate that the membrane had a few defects larger than the pore size.…”
Section: Resultsmentioning
confidence: 99%
“…Saboor et al reported that B-ZSM-5 membranes fabricated from clear synthesis solutions (H 2 O/SiO 2 = 64) on seeded α -alumina discs preferentially permeated ethanol from water, showing a relatively high permeation flux of 1110 g·m −2 ·h −1 but a low separation factor of 13.9. Recently, Chai and co-workers observed a high permeation flux of 2600 g·m −2 ·h −1 and a moderate separation factor of 55 using a B-ZSM-5 membrane synthesized from a dilute solution (H 2 O/SiO 2 = 600) on seeded inexpensive macroporous α -alumina tube [ 217 ]. It suggests that the PV performance for B-ZSM-5 membranes is greatly dependent on their preparation conditions.…”
Section: Membrane Materials For Ethanol Recoverymentioning
confidence: 99%